Kompres Hangat untuk Pasca Operasi Sectio Caesarean - R. Krowa, Yuliana R.; Savitri, Wenny (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Back ground : Pain is an unpleasant emotional and sensory experience which is caused by the actual damage of body tissue. The pain experience by mother after Caesarean Section highly affects the ability of mother to take care and breast-feed the baby. It leads to dysfunctional family process. Many complementary therapies can be used to decrease patientsâ pain scale. One of the therapies is warm compress technique, but unfortunately the effectiveness of this technique has not been identified in Sleman District General Hospital. Objective : The study aimed to identify the effectiveness of the warm compress technique on patientsâ pain scale following Caesarean Section surgery. Method : A quasy-experiment with pre-test and post-test with control group design was utilized in this study. 15 participants who met inclusion criteria were recruited for each group. The Numerical Rating Scale is used to measure the pain scale, where the pain is measured before and after the intervention within 3 days. Data analysis used was Independent Sample t-test with p < 0.05. Result : The result of Independent Sample t-test between intervention group and controlled group is (t = -3.445, p = 0.002). The average of pain scale in the intervention group is 5.80 as compared to control group as much as 6.87 (scale of 1-10). Conclusion : Warm compress technique significantly can decrease patientsâ pain scale following Caesarean Section surgery. Therefore, the practical use of this technique for such population is necessary to be implemented as one of complementary therapies in clinical setting. Keywords: Warm compress technique, pain, complementary therapy.